2022
DOI: 10.3390/jof8030305
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Candidemia Is Higher in COVID-19 versus Non-COVID-19 Patients, but Not Driven by Intrahospital Transmission

Abstract: There is scarce information on the actual incidence of candidemia in COVID-19 patients. In addition, comparative studies of candidemia episodes in COVID-19 and non-COVID-19 patients are heterogeneous. Here, we assessed the real incidence, epidemiology, and etiology of candidemia in COVID-19 patients, and compared them with those without COVID-19 (2020 vs. 2019 and 2020, respectively). We also genotyped all C. albicans, C. parapsilosis, and C. tropicalis isolates (n = 88), causing candidemia in both groups, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 49 publications
(65 reference statements)
5
23
6
1
Order By: Relevance
“…Contrary to a previous study by Machado et al, only one isolate was found that was resistant to antifungal drugs [4]. Similarly, Candida auris, whose first described case occurred in our institution [20], was not found, although its incidence is high in some studies [21].…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Contrary to a previous study by Machado et al, only one isolate was found that was resistant to antifungal drugs [4]. Similarly, Candida auris, whose first described case occurred in our institution [20], was not found, although its incidence is high in some studies [21].…”
Section: Discussioncontrasting
confidence: 86%
“…Conflicting data exist regarding the incidence of candidemia among patients with severe COVID-19 [ 1 , 2 , 3 , 4 , 5 ]. In this study, we analyzed the occurrence of invasive candidiasis in a cohort of 264 patients during an 11-month period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an increase in incidence of candidemia among critically ill COVID-19 patients has been reported from different parts of the world. [ 6 , 7 , 8 , 10 , 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the higher incidence was not driven by patient-to-patient Candida spp. transmission suggesting that individual risk factors might also contribute to the rising number of Candida infections ( Machado et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%